Phenolic Content and Antioxidant, Antihyperlipidemic, and Antidiabetogenic Effects of Opuntia dillenii Seed Oil - Mohamed Bouhrim; Nour Elhouda Daoudi; Hayat Ouassou; Amina Benoutman; El Hassania Loukili; Abderrahim Ziyyat; Hassane Mekhfi; Abdelkhaleq Legssyer; Mohammed Aziz; Mohamed Bnouham (The Scientific World Journal)
Opuntia dillenii (Ker-Gawl.) Haw. is a medicinal plant that is widely used by the Moroccan population to treat many diseases, thanks to its richness in bioactive molecules. This study aims to evaluate the total phenolic content and antioxidant, antihyperlipidemic, and antidiabetogenic activities of O. dillenii seeds oil (ODSO), in vivo. The 2,2-diphenyl-1-picrylhydrazyl (DPPH) scavenging assay and the Folin–Ciocalteu method were applied in this study to determine antioxidant activity and total phenolic content of ODSO, respectively. The antihyperlipidemic effect of the ODSO (2 ml/kg) was evaluated in the high-fat diet-fed albino mice, relying on lipid profile, blood glucose, and growth performance variations. Moreover, the preventive effect of ODSO was evaluated against alloxan monohydrate-induced diabetes in albino mice. ODSO had the highest total phenolic content (518.18 ± 14.36 mg EAC/kg) and DPPH scavenging activity (IC50 = 0.38 ± 0.08 mg/mL). Furthermore, ODSO showed a significant antidiabetogenic effect by reducing bodyweight loss, blood sugar level rise, and mortality rate caused by alloxan in albino mice. Then, ODSO has exhibited a significant antihyperlipidemic effect by improving the lipid profile disorder and glucose level rise in the blood, produced by the high-fat diet-fed albino mice. Results suggest that antidiabetogenic and antihyperlipidemic activities of ODSO correlate to the phenolic content and antioxidant activity of this oil. Hence, this plant could be a significant source of medically important critical compounds.